2014
DOI: 10.1590/1982-0194201400062
|View full text |Cite
|
Sign up to set email alerts
|

Construção da Matriz de Competência Profissional do enfermeiro em emergências

Abstract: Objective: To propose a Professional Competency Matrix for the nurse working in emergency services. Methods: This is a descriptive study that details quantitative, nominal and conceptual aspects of the proposed competencies. The creation of the Competency Matrix was based on the professional experience of the researchers, empirical evidence, and specialized literature. Results: The proposed Professional Competency Matrix was composed of eight basic competencies, with 31 associated competencies attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
0
11
0
6
Order By: Relevance
“…Therefore, it was considered pertinent, at this stage of the research, to use the first source of information, i.e., the Content. Thus, this study is in line with the abovementioned studies (3)(4) since it tried to continue the initial procedures to develop an instrument of measurement to evaluate the professional competencies of nurses working in emergency services.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, it was considered pertinent, at this stage of the research, to use the first source of information, i.e., the Content. Thus, this study is in line with the abovementioned studies (3)(4) since it tried to continue the initial procedures to develop an instrument of measurement to evaluate the professional competencies of nurses working in emergency services.…”
Section: Introductionmentioning
confidence: 56%
“…In this research, validity evidence was based on the content of the Identifying Issues proposed for the competent performance of nurses in the emergency services. These questions were constructed from the definitions of each Basic and Associated Competence to describe the desired attitudes/behaviors in the daily life of this professional (3)(4) . The theoretical-logical model created by the authors was exemplified by the Basic Competence: Care Performance and the Associated Competence: Sense of Urgency (Figure 1).…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, seeking an independent, reactive, entrepreneurial professional profile generated the need to develop professional skills related to the various health contexts, according to the requirements requested for each area of activity. 1 In the field of Primary Health Care (PHC), many practices have been developed through the Basic Health Units (BHU) with Family Health teams (FHt), which is a proposal for reorienting the health care model, from primary care, in line with the principles of the Unified Health System (UHS), focusing on the consolidation of this model to meet the transformations of the health scenario. 2 Given this, the Family Health Strategy (FHS) proposes a new way and new manners of working health, with the family as the center of attention, through a humanized vision in the process of intervention to users, expanding comprehensive health care, acting preventively.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that certain competencies such as autonomy, communication, interpersonal relationship, leadership, risk control, emotional balance, among others focused during these professionals' training and practice, may reflect positively on their social relations. (23,24) In this study, data on the lowest score in the social domain of nurses' QoL were in contrast, even though organizational support was provided in the work environment. In opposition, studies indicated that organizational support is the result of a management model in which nurses can exercise their work process and manage with well-defined criteria.…”
Section: Discussionmentioning
confidence: 64%